2020
DOI: 10.1002/aqc.3483
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term catch trends and risk assessment of the Critically Endangered white‐spotted wedgefish (Rhynchobatus djiddensis) from South Africa

Abstract: The white‐spotted wedgefish (Rhynchobatus djiddensis) is a Critically Endangered shark‐like ray in the family Rhinidae. Throughout its Western Indian Ocean distribution, it is targeted for its valuable meat and fins and is reported to have undergone major population declines. However, there remains a need for species specific time‐series data to accurately assess localized population declines. This study used two independent long‐term (37 and 40 years) time‐series catch data from competitive shore angling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A recent trend shows that the fins of wedgefishes are becoming more common in the shark fin trade (Fields et al 2018). Declines of R. djiddensis have been observed in South Africa (Daly et al 2021) and in Mozambique, where this species was previously reported to be abundant (Pierce et al 2008;Hopkins 2011). In South Africa, R. djiddensis was caught as bycatch by demersal prawn trawlers operating on the Thukela Bank (located off central KwaZulu-Natal), until the fishery closed in 2002 (Jordaan et al 2021).…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent trend shows that the fins of wedgefishes are becoming more common in the shark fin trade (Fields et al 2018). Declines of R. djiddensis have been observed in South Africa (Daly et al 2021) and in Mozambique, where this species was previously reported to be abundant (Pierce et al 2008;Hopkins 2011). In South Africa, R. djiddensis was caught as bycatch by demersal prawn trawlers operating on the Thukela Bank (located off central KwaZulu-Natal), until the fishery closed in 2002 (Jordaan et al 2021).…”
Section: Case Studymentioning
confidence: 99%
“…Additionally, wedgefishes are targeted by foreign vessels off eastern Africa (offshore of Mozambique, Tanzania and Madagascar) (Kyne et al 2020). Thus, for R. djiddensis the threat to the population seems not to be within South Africa, where this species is protected, but rather in neighbouring countries where the species is under severe threat of exploitation (Kyne et al 2020;Daly et al 2021). Recently, species in the family Rhinidae have shown severe population declines globally, resulting in 9 of the 10 species (90%) being assessed as Critically Endangered on the IUCN Red List (Kyne et al 2020), including R. djiddensis (Kyne et al 2019).…”
Section: Case Studymentioning
confidence: 99%
“…In SA, its population has been described as “Endangered”, with the main threats in KZN being fisheries— e.g. , shore angling—and the bather protection nets (locally known as shark nets) located south of the study area ( Daly et al, 2020 ; Pradervand et al., 2007 ). Since the mature individuals of this species can move long distances, they are also vulnerable to threats across the border in Mozambique ( Jordaan et al, 2021 ; SAAMBR, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rhynchobatus djiddensis is known to be most abundant in central and southern KZN during summer and to concentrate northwards, possibly into Mozambique, during winter ( Daly et al, 2020 ; Jordaan et al, 2021 ). The current findings suggest that at least some wedgefishes remain in SA waters during winter, where they are under the protection of the iSimangaliso MPA, rather than being exposed to threats in Mozambique.…”
Section: Discussionmentioning
confidence: 99%
“…In response to potential negative shark–human encounters and the increasing socio‐economic pressure associated with these encounters, shark culls are often government‐instituted programmes that involve killing sharks with the use of beach nets (also known as shark nets) and drumlines (or other types of baited hooks) to maximize beachgoer safety (Ikehara, 1961; Tester, 1968; Tester, 1969; Government of Western Australia, 2014; Guyomard et al, 2019). However, with continued trends in elasmobranch population decline (Worm et al, 2013; Pacoureau et al, 2021) and the substantial by‐catch of other endangered, threatened, or protected (ETP) species in association with beach nets (Brazier et al, 2012; Atkins, Cliff & Pillay, 2013), such as the Indian Ocean humpback dolphin ( Sousa plumbea ; Atkins et al, 2016) and the white‐spotted wedgefish ( Rhynchobatus djiddensis ; Daly et al, 2021), there is an urgent need to develop and implement more ecologically responsible solutions. One such approach is the implementation of less‐invasive exclusion barriers, such as exclusion nets (as noted in McPhee, 2012) and the SharkSafe Barrier™ (O'Connell et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%